XRF Analysis of Heavy Metals for Surface Soil of Qarun Lake and Wadi El Rayan in Faiyum, Egypt - El-Bahi, Samia M.; Sroor, Amany T.; Arhoma, Najat F.; Darwish, Saher M. (Scientific Research, 2013)
The environmental pollution with some heavy metals for twenty four surface soil samples collected from Qarun Lake and Wadi El Rayan region in Faiyum, Egypt utilizing X-ray fluorescence (XRF) spectroscopy was measured. The concentrations of 13 elements Cr, Ni, Cu, Zn, Zr, Rb, Y, Ba, Pb, Sr, Ga, V and Nb were determined. The elemental concentrations were compared with the normal values and other studies in different locations from the world. The correlation between elements appears that pollution inside the investigated lake and Wadi result from different sources of contamination present inside them. The results establish a database reference of radioactivity background levels around these regions.
Keywords: XRF; Heavy Metals; Surface Soil; Faiyum